The maker of swans : a novel - O'Donnell, Paraic (Tin House, 2022)
"In the dead of night, shots ring out over the grounds of a sprawling English estate. The world-weary butler Eustace recognizes the gunman-his longtime employer, Mr. Crowe-and knows he must think and act quickly. Who is the man lying dead on the lawn? Who is the woman in his company? Can he clean up his master's mess like he always has before? Or will this bring a new kind of reckoning? Mr. Crowe was once famed for his gifts-unaccountable gifts, known only to the members of a secretive order. Protected and privileged, he was courted by countesses and great men of letters. But he has long since retreated from that glittering world, living alone but for Eustace and Clara, his mysterious young ward. He has been content to live quietly, his great library gathering dust and his once magnificent gardens growing wild. He has left the past behind. Until now. Because there are rules, even for Mr. Crowe and his kind, that cannot be broken. And this single night of passion and violence will have consequences, stirring shadows from the past and threatening those in his care. He and the faithful Eustace will be tested as never before. So too will Clara, whose own extraordinary gifts remain hidden, even from herself. If she is to save them all, she must learn to use them quickly and unlock the secret of who she is. It is a secret beyond imagining. A secret that will change everything"--